The Effects of Fin Cant Angle and Fin Height on the Performance of a Low Altitude Rocket - Zuraidah Salleh; Ahmad Hussein Abdul Hamid; Alif Abni Adnan; Mohamad Amirul Muhammad; Szymon Gwozdz (International Journal of Integrated Engineering, 2024)
It is known that aerodynamics play an important role in the stability of a rocket. Stability has been defined as a system's tendency to recover or revert to its initial state following a perturbation. The location of the centre of gravity and the centre of pressure fundamentally determines the stability of the rocket. One of the main issues with a small rocket is that the viscous effect becomes more prominent, which may significantly alter the pressure distribution around its body.  Hence, when the scale is reduced, the study of aerodynamics effect on the rocket’s centre of pressure (thus stability) becomes more crucial. In this present study, we investigate the stability of a low-altitude rocket by determining the effect of spin stabilisation on rocket stability. The locations of centre gravity and centre pressure are determined in this study using the Barrowman equations. It was found that a fin height of 4 cm produces the ideal static margin of approximately 1.5. Furthermore, largest fin cant of 10° yields highest apogee. In general, the rocket's static stability improves when the fin height is increased, while the fin cant angle affects the dynamic stability.